A stabilized virtual coupling scheme for a train set with heterogeneous braking dynamics capability. (January 2023) - Su, Shuai; She, Jiangfeng; Wang, Di; Gong, Siyuan; Zhou, Yang
Abstract: Virtual coupling (VC) is an advanced technology in train control systems, which enables trains to run information with a small tracking interval. Hence, it can significantly increase the capacity of rail transit. Similar to the vehicle platooning, most established VC approaches select the constant time/spacing gap commonly as the spacing policy but regards the relative braking distance as a constraint. These spacing policy diminish the priority of safety concern in train control systems due to the severity of incidents and economic loss. Motivated by this research gap, in this paper, we designed a stabilized virtual coupling scheme for a train set with heterogeneous braking dynamics capability. Specifically, a relative braking distance based spacing policy is introduced according to the braking dynamics capability of the train, which is a typical characteristic that distinguishes it from the vehicle platoon model. A linear control architecture suitable for the virtual coupled train set (VCTS) is designed to maintain the equilibrium spacing. Sufficient conditions to ensure the local stability are derived and obtained in this paper. The impact of braking dynamics capability on the string stability is analyzed in terms of acceleration and spacing difference respectively in the frequency domain by using the Laplacian transformation. For the former, the necessary and sufficient conditions to ensure the string stability are given, and for the latter, a numerical traversal method to summarize the impact of the heterogeneous braking dynamics capability on string stability is given based the former. Two sets of test examples are given, proving the correctness of the necessary and sufficient conditions of the former and the applicability of the research method of the latter, respectively. Highlights: Virtual coupled train set with heterogeneous braking dynamics capability. Sufficient conditions to ensure the local stability of the controller. The impact of braking dynamics capability on the string stability.